Pengaruh Tebal Deposit Lasan Terhadap Properti Lapisan Menggunakan Elektroda HV 450 - Syaripuddin Syaripuddin; Sopiyan Sopiyan; Alpi Cahyadi; Sigit Dwi Yudanto; Muhammad Yunan Hasbi; Ferry Budhi Susetyo (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2023)
This study investigates the effect of the increased welding layers welded by the SMAW process on distorsion, thickness, microstructure, hardness, and corrosion. The method used in this research is experimental. Low-carbon steel with a size of 150x10x10 mm was welded by the SMAW technique using an HV 450 electrode. Variations in the welding layers are single, double, and triple. The three variations of the samples were observed with a digital camera and an optical microscope. Moreover, samples were tested with a hardness tester. Corrosion testing was also carried out to determine the corrosion rate of the layers formed. The results showed that the number of SMAW welding layers affected the thickness, phase, hardness, and corrosion rate. The hardness of one layer is less than that of thicker specimens, while the corrosion rate of three layers is lower than that of less-thick samples.